Dampak Pembelajaran Online Bagi Siswa Sekolah Dasar - Shintia Puspita Dewi; Sekar Dwi Ardianti; Muhammad Noor Ahsin (WASIS : Jurnal Ilmiah Pendidikan, 2021)
The purpose of this study is to analyze the impact of online learning on elementary school students 1 Barongan Kudus.The research method used is qualitative. Research data collection is done through the provision of questionnaires, observations, interviews, and documentation. The research was conducted in the odd semester of the 2021/2021 academic year. The research data were collected using observation and interview techniques. Research sources include teachers, students, and parents of elementary school students 1 Barongan Kudus. Data checking was carried out using triangulation to increase the degree of confidence and accuracy of the data. Triangulation is done with three strategies, namely source triangulation, method triangulation, and time triangulation. The data analysis technique used is the Miles and Huberman analysis technique.The results showed that teachers, students and parents were unable to communicate directly and online learning required all parties to communicate via WhatsApp..